Effects of different transcranial magnetic stimulations on neuropathic pain after spinal cord injury - Yang, Chuanmei; Bi, Yunfeng; Hu, Luoman; Gong, Lili; Li, Zhanfei; Zhang, Nanyang; Wang, Qiang; Li, Jiang (Frontiers in Neurology, 2023)
Introduction: Repetitive transcranial magnetic stimulation (rTMS) is an effective non-invasive cortical stimulation technique in the treatment of neuropathic pain. As a new rTMS technique, intermittent theta burst stimulation (iTBS), is also effective to relieve pain. We aimed to establish the pain-relieving effectiveness of different modalities on neuropathic pain. The study was conducted in individuals with spinal cord injury (SCI) and different modalities of rTMS.Methods: Thirty-seven individuals with SCI were randomly allocated to 3 groups, in which "iTBS" group received iTBS, "rTMS" group received 10 Hz rTMS, "iTBS + rTMS" group received iTBS and 10 Hz rTMS successively of the primary motor cortex 5 days a week for 4 weeks, and they all underwent the full three procedures. The primary outcome measure was change in the visual analog scale (VAS), secondary outcomes were measures by Hamilton Rating Scale for Depression (HAM-D) and the Pittsburgh Sleep Quality Index (PSQI). All the outcomes were evaluated at 1 day before stimulation (Baseline), 1 day after the first week of stimulation (S1), 1 day after the last stimulation (S2).Results: VAS score showed significant pain improvement after 4 weeks stimulation (p = 0.0396, p = 0.0396, and p = 0.0309, respectively) but not 1 week stimulation. HAM-D scores declined, but the decreases were not significant until 4 weeks later (p = 0.0444, p = 0.0315, and p = 0.0447, respectively). PSQI scores were also significantly decreased after 4 weeks stimulation (p = 0.0446, p = 0.0244, and p = 0.0088, respectively). Comparing the 3 modalities, VAS, HAM-D, and PSQI scores at S1 showed no differences, and at S2, VAS score showed significant differences (p = 0.0120, multiple comparison showed significant differences between iTBS and iTBS + rTMS, p = 0.0091), while HAM-D and PSQI scores showed no difference. Discussion: The primary and secondary outcomes all showed significant improvement, indicating that 3 different modalities were all effective to relieve the pain. However, not all the 3 stimulations